Interrelationships among linear sprinting, curve sprinting, change-of-direction ability, and power output in elite female soccer players - Loturco, I.; Mcguigan, M. R.; Requena, B.; Tavares, L. D.; Mercer, V. P.; Moura, T. B. M. A.; Oliveira, L. P.; Pereira, L. A.; Bishop, C. (The Journal of Strength and Conditioning Research, 2026)
This study investigated the relationships among linear sprinting speed, curve sprinting (CS), change-of-direction (COD) ability, and lower-limb power output in elite female soccer players. Fifty-one athletes (21.4 ± 6.4 years; 1.66 ± 0.07 m; 51.5 ± 13.5 kg) competing in the Brazilian first division performed squat jump and countermovement jump, linear sprints (10- and 20-m sprints), a zigzag COD test, a CS test (in both directions: right and left, with the fastest side named the "good side" and the slowest side named the "weak side"), and jump squats (JS) with loads corresponding to 40 and 60% of their body mass. Sprint momentum (SM) and COD deficit were calculated. Correlation analyses revealed moderate-to-very-large significant relationships between jump height, sprint speed, CS, and COD performance ( r -values ranging from 0.37 to 0.93). Jump squat power was significantly associated with linear sprinting, COD, and CS speed ( r -values ranging from 0.39 to 0.71). In addition, no association was found between SM and COD deficit. These results suggest that linear sprint speed, rather than momentum, is a more decisive factor in COD efficiency among elite female soccer players. Coaches should consider individualized training strategies focused on improving deceleration and reacceleration capacities, especially for faster athletes in linear sprints. Overall, the integrated assessment of linear sprints, CS, and COD speed, alongside JS power, provides a comprehensive perspective on speed-power profiles in elite female soccer and may help guide more effective training prescriptions and performance monitoring in this specific population.